Average and competitive analysis of latency and power consumption of a queuing system with a sleep mode - Herlich, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Energy-Efficient Computing and Networking, e-Energy'12, Madrid, Spain, May 9-11, 2012)

Energy Efficient Clustering using a Wake-up Receiver - Blanckenstein, Johannes; Klaue, Jirka; Karl, Holger (European Wireless 2012 - 18th European Conference 2012, April 18-20, 2012, Poznan, Poland.)

On Local Separation of Processing and Storage in Infrastructure-as-a-Service - Künsemöller, Jörn; Karl, Holger (Economics of Grids, Clouds, Systems, and Services - 9th International Conference, GECON 2012, Berlin, Germany, November 27-28, 2012. Proceedings)

Efficiency of On-Path and Off-Path Caching Strategies in Information Centric Networks - Dräxler, Martin; Karl, Holger (2012 IEEE International Conference on Green Computing and Communications, Conference on Internet of Things, and Conference on Cyber, Physical and Social Computing, GreenCom/iThings/CPSCom 2012, Besancon, France, November 20-23, 2012)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks, Workshop Proceedings, Clearwater Beach, FL, USA, October 22-25, 2012)

Cooperating base station set selection and network reconfiguration in limited backhaul networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger; Kellerer, Wolfgang (23rd IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2012, Sydney, Australia, September 9-12, 2012)

Using OMNeT++ for energy optimization simulations in mobile core networks - Dräxler, Martin; Beister, Frederic; Kruska, Stephan; Aelken, J.; Karl, Holger (International ICST Conference on Simulation Tools and Techniques, SIMUTOOLS '12, Sirmione-Desenzano, Italy, March 19-23, 2012)

Quantization techniques for accurate soft message combining - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (2012 IEEE Wireless Communications and Networking Conference, WCNC 2012, Paris, France, April 1-4, 2012)

Efficient cooperative relaying in wireless multi-hop networks with commodity WiFi hardware - Volkhausen, Tobias; Dridger, Kornelius; S. Lichte, Hermann; Karl, Holger (10th International Symposium on Modeling and Optimization in Mobile, Ad Hoc and Wireless Networks (WiOpt), Paderborn, Germany, May 14-18, 2012)

Model-driven Performance Engineering of Self-Adaptive Systems: A Survey - Becker, Matthias; Luckey, Markus; Becker, Steffen (Proceedings of the International Conference on Quality of Software Architecture)

Towards an Automatic Service Discovery for UML-based Rich Service Descriptions - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the ACM/IEEE 15th International Conference on Model Driven Engineering Languages and Systems (MODELS'12))
Service-oriented computing (SOC) promises to solve many issues in the area of distributed software development, e.g. the realization of the loose coupling pattern in practice through service discovery and invocation. For this purpose, service descriptions must comprise structural as well as behavioral information of the services otherwise an accurate service discovery is not possible. We addressed this issue in our previous paper and proposed a UML-based rich service description language (RSDL) providing comprehensive notations to specify service requests and offers. However, the automatic matching of service requests and offers specified in a RSDL for the purpose of service discovery is a complex task, due to multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different underlying ontologies or different levels of granularity in the specification itself resulting in complex mappings between service requests and offers. In this paper, we present an automatic matching mechanism for service requests and offers specified in a RSDL that overcomes the underlying heterogeneity of the service partners.

Quasar 3.0 - A Situational Approach to Software Engineering - Kremer, Marion; Engels, Gregor; Hofmann, Alexander; Hohwiller, Jörg; E. Nandico, Oliver; Nötzold, Thomas; Prott, Karl; Schlegel, Diethelm; Seidl, Andreas; Wolf, Thomas

Towards higher-dimensional topological self-stabilization: A distributed algorithm for Delaunay graphs - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Theoretical Computer Science)
This article studies the construction of self-stabilizing topologies for distributed systems. While recent research has focused on chain topologies where nodes need to be linearized with respect to their identiers, we explore a natural and relevant 2-dimensional generalization. In particular, we present a local self-stabilizing algorithm DStab which is based on the concept of \local Delaunay graphs" and which forwards temporary edges in greedy fashion reminiscent of compass routing. DStab constructs a Delaunay graph from any initial connected topology and in a distributed manner in time O(n3) in the worst-case; if the initial network contains the Delaunay graph, the convergence time is only O(n) rounds. DStab also ensures that individual node joins and leaves aect a small part of the network only. Such self-stabilizing Delaunay networks have interesting applications and our construction gives insights into the necessary geometric reasoning that is required for higherdimensional linearization problems.Keywords: Distributed Algorithms, Topology Control, Social Networks

Towards an Automatic Service Discovery for UML-based Rich Service Descriptions - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the ACM/IEEE 15th International Conference on Model Driven Engineering Languages and Systems (MoDELS))
Service-oriented computing (SOC) promises to solve many issues in the area of distributed software development, e.g. the realization of the loose coupling pattern in practice through service discovery and invocation. For this purpose, service descriptions must comprise structural as well as behavioral information of the services otherwise an accurate service discovery is not possible. We addressed this issue in our previous paper and proposed a UML-based rich service description language (RSDL) providing comprehensive notations to specify service requests and offers.However, the automatic matching of service requests and offers specified in a RSDL for the purpose of service discovery is a complex task, due to multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different underlying ontologies or different levels of granularity in the specification itself resulting in complex mappings between service requests and offers. In this paper, we present an automatic matching mechanism for service requests and offers specified in a RSDL that overcomes the underlying heterogeneity of the service partners.

Towards a Framework for the Integration of Modeling Languages - Arifulina, Svetlana (Proceedings of the Doctoral Symposium of the 5th International Conference on Software Language Engineering 2012, Dresden, Germany (SLE (Doctoral Symposium)))
In software markets of the future, customer-specific software will be developed on demand from distributed software and hardware services available on world-wide markets. Having a request, services have to be automatically discovered and composed. For that purpose, services have to be matched based on their specifications. For the accurate matching, services have to be described comprehensively that requires the integration of different domain-specific languages (DSLs) used for functional, non-functional, and infrastructural properties. Since different service providers use plenty of language dialects to model the same service property, their integration is needed for the matching. In this paper, we propose a framework for integration of DSLs. It is based on a parameterized abstract core language that integrates key concepts needed to describe a service. Parts of the core language can be substituted with concrete DSLs. Thus, the framework serves as a basis for the comprehensive specification and automatic matching of services.

Tiara: A self-stabilizing deterministic skip list and skip graph - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Theoretical Computer Science)
We present Tiara — a self-stabilizing peer-to-peer network maintenance algorithm. Tiara is truly deterministic which allows it to achieve exact performance bounds. Tiara allows logarithmic searches and topology updates. It is based on a novel sparse 0-1 skip list. We then describe its extension to a ringed structure and to a skip-graph.Key words: Peer-to-peer networks, overlay networks, self-stabilization.

Model-driven specification of adaptive cloud-based systems - Nagel, Benjamin; Gerth, Christian; Yigitbas, Enes; Christ, Fabian; Engels, Gregor (Proceedings of the 1st International Workshop on Model-Driven Engineering for High Performance and CLoud computing co-located with 15th International Conference on Model Driven Engineering Languages and Systems {(MODELS} 2012), Innsbruck, Austria, October 01 - 05, 2012)

Entwicklung eines Monitoring- und Adaptionskonzeptes für Geschäftsprozesse in service-orientierten Systemen - Yigitbas, Enes

Stabilization, Safety, and Security of Distributed Systems
SSS is an international forum for researchers and practitioners in the design and development of distributed systems with self-properties: (classical) self-stabilizing, self-configuring, self-organizing, self-managing, self-repairing, self-healing, self-optimizing, self-adaptive, and self-protecting. Research in distributed systems is now at a crucialpoint in its evolution, marked by the importance of dynamic systems such as peer-to-peer networks, large-scale wireless sensor networks, mobile ad hoc networks, cloud computing, robotic networks, etc. Moreover, new applications such as grid and web services, banking and e-commerce, e-health and robotics, aerospace and avionics, automotive, industrial process control, etc. have joined the traditional applications of distributed systems. The theory of self-stabilization has been enriched in the last 30 years by high quality research contributions in the areas of algorithmic techniques, formal methodologies, model theoretic issues, and composition techniques. All these areas are essential to the understanding and maintenance of self-properties in fault-tolerant distributed systems.

Smoothed analysis of left-to-right maxima with applications - Damerow, Valentina; Manthey, Bodo; Meyer auf der Heide, Friedhelm; Räcke, Harald; Scheideler, Christian; Sohler, Christian; Tantau, Till (Transactions on Algorithms)
A left-to-right maximum in a sequence of n numbers s_1, …, s_n is a number that is strictly larger than all preceding numbers. In this article we present a smoothed analysis of the number of left-to-right maxima in the presence of additive random noise. We show that for every sequence of n numbers s_i ∈ [0,1] that are perturbed by uniform noise from the interval [-ε,ε], the expected number of left-to-right maxima is Θ(&sqrt;n/ε + log n) for ε>1/n. For Gaussian noise with standard deviation σ we obtain a bound of O((log3/2 n)/σ + log n).We apply our results to the analysis of the smoothed height of binary search trees and the smoothed number of comparisons in the quicksort algorithm and prove bounds of Θ(&sqrt;n/ε + log n) and Θ(n/ε+1&sqrt;n/ε + n log n), respectively, for uniform random noise from the interval [-ε,ε]. Our results can also be applied to bound the smoothed number of points on a convex hull of points in the two-dimensional plane and to smoothed motion complexity, a concept we describe in this article. We bound how often one needs to update a data structure storing the smallest axis-aligned box enclosing a set of points moving in d-dimensional space.